2020
DOI: 10.20944/preprints202002.0093.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paravertebral Block Versus Preemptive Ketamine Effect on Pain Intensity after Posterolateral Thoracotomies: A Randomized Controlled Trial

Abstract: Severe postoperative pain affects most patients after thoracotomy and is a risk factor for post-thoracotomy pain syndrome (PTPS). This randomized controlled trial compared preemptively administered ketamine versus paravertebral block (PVB) versus control in patients undergoing posterolateral thoracotomy. The primary outcome was acute pain intensity on the visual analog scale (VAS) on the first postoperative day. Secondary outcomes included morphine consumption, patient satisfaction, and PTPS assessment with Ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Only a few studies have presented the alleviation of persistent postoperative pain due to regional anesthesia techniques [ 20 , 21 , 22 ]. In these studies, the paravertebral block or the epidural anesthesia reduced chronic pain intensity in patients after a thoracotomy or breast surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have presented the alleviation of persistent postoperative pain due to regional anesthesia techniques [ 20 , 21 , 22 ]. In these studies, the paravertebral block or the epidural anesthesia reduced chronic pain intensity in patients after a thoracotomy or breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This inventory is multi-dimensional and covers many aspects of chronic pain. We used the NPSI in our previous studies for persistent pain measurement [ 17 , 22 ]. Moreover, NPSI were used by other authors to measure persistent postoperative pain [ 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural block showed the greatest tendency for reduction in chronic postoperative pain while other modalities, including continuous wound infiltration and intercostal nerve block, were less efficacious [19, 31]. Previous studies investigating paravertebral blocks have suggest that they provide efficacy equivalent to epidural for management of thoracic surgical pain, and paravertebral blocks may also reduce the incidence and/or intensity of chronic postoperative pain [27, 32, 33].…”
Section: Evidence For the Role Of Regional Anaesthesia In The Prevention Of Chronic Postoperative Painmentioning
confidence: 99%
“…Results from previous studies have confirmed the effectiveness of TPVB in acute post-thoracotomy pain control (42,43). Borys et al compared between TPVB and preemptive bolus ketamine in patients undergoing posterolateral thoracotomies and reported that TPVB was superior to ketamine in reducing pain intensity and morphine consumption (44). Ketamine has only moderate effect on acute postoperative pain (36,40), therefore, its advantage is less likely to be shown when combined with other multimodal analgesia techniques (25,45,46).…”
Section: Probablity Of Absence Of Painmentioning
confidence: 86%